Trimethyllysine, a trimethylamine N-oxide precursor, predicts the presence, severity, and prognosis of heart failure - Zong, Xiao; Fan, Qin; Yang, Qian; Pan, Roubai; Zhuang, Lingfang; Xi, Rui; Zhang, Ruiyan; Tao, Rong (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims: Intestinal flora metabolites are associated with cardiovascular diseases including heart failure (HF). The carnitine precursor trimethyllysine (TML), which participates in the generation of the atherogenic-related metabolite trimethylamine N-oxide (TMAO), was found to be related to poor prognosis in patients with cardiovascular diseases. The aim of the present study was to examine the relationship between TML and stable chronic HF. Methods and Results: 956 subjects including 471 stable chronic HF and 485 non-HF patients were enrolled in the present cohort study and subjects with stable HF were followed up for 2.0 ± 1.1 years. Serum levels of TML and TMAO were measured by liquid chromatography mass spectrometry in tandem. TML levels were significantly elevated in patients with HF compared with non-HF patients and were positively correlated with N-terminal pro-brain natriuretic peptide levels (r = 0.448, P < 0.001). TML was associated with the presence of HF after adjusting for age, sex, complications, traditional clinical factors and TMAO (tertile 3 [T3], adjusted odds ratio [OR] 1.93, 95% confidence interval [CI] 1.19-3.13, P = 0.007). In patients with HF, increased TML levels were associated with a composite endpoint of cardiovascular death and HF hospitalization during follow-up (T3, adjusted hazard ratio [HR] 1.93, 95% CI 1.27-2.93, P = 0.002). Increased TML levels indicated a higher risk of cardiovascular death, re-hospitalization, and all-cause mortality. Conclusions: Serum TML levels were associated with the presence and severity of HF in all subjects. High levels of TML can indicate complications and poor prognosis in HF patients.